The effectiveness of audio visual aids in enhancing the reading skills among the year 3 students / Siti Rosmah Hashim - Hashim, Siti Rosmah (Faculty of Education, 2015)
The main purpose of this study is to evaluate the effectiveness of audio visual aids in enhancing the reading skills among the Year 3 students. The research is to find out whether the technique manages to attract the students’ attention and interest during learning and teaching session. The subject involved were 30 students of Year 3 Bijak in Sekolah Kebangsaan Labohan Dagang, 42700 Banting, Selangor. Firstly, a checklist form containing data of students’ attitude during teaching and learning session was prepared by the teacher in identifying how much boredom the students were in the first observation and the effectiveness of the materials after they were used. Next, two sets of students’ tests (Pre-Test and Post Test) will be analysed in getting the percentage of the students’ understanding during teaching and learning hours. The finding shows that the students’ performance in understanding the content of the lesson has improved after using the audio visual aids because it was able to make them learn in a happy and fun situation.